2021
DOI: 10.1002/ps.6361
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of the neonicotinoid seed treatment ban on oilseed rape production – what can be learnt from the Swedish experience?

Abstract: There has been great concern about negative effects on crop production resulting from the ban on insecticide seed treatments containing neonicotinoids. I examine how the neonicotinoid ban has affected crop protection and crop production in oilseed rape (Brassica napus L.) using Sweden as a case study and compare the Swedish situation with that in leading countries growing winter and spring oilseed rape, respectively. The cropping area of winter and spring oilseed rape in Sweden has increased by approximately 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 47 publications
0
22
0
Order By: Relevance
“…Since the resource base is an annual agricultural crop delineated by human managed decisions, we can rule out the hypothesis that bottom‐up forces, in the form of long‐term variation and delayed feedbacks in plant quality, are driving the population cycles for P. chrysocephala in annual winter oilseed rape fields. Though large‐scale changes in agriculture can dampen pest population cycles (Bell et al, 2012), we see no such shifts in the amplitude and periodicity of P. chrysocephala cycles that could be attributed to changes in the area planted to winter oilseed rape in Scania (Figure S8), overall pesticide use (Figure S9) or policy‐driven changes, such as the ban of neonicotinoid seed treatments since 2013 (Lundin, 2021).…”
Section: Discussionmentioning
confidence: 78%
“…Since the resource base is an annual agricultural crop delineated by human managed decisions, we can rule out the hypothesis that bottom‐up forces, in the form of long‐term variation and delayed feedbacks in plant quality, are driving the population cycles for P. chrysocephala in annual winter oilseed rape fields. Though large‐scale changes in agriculture can dampen pest population cycles (Bell et al, 2012), we see no such shifts in the amplitude and periodicity of P. chrysocephala cycles that could be attributed to changes in the area planted to winter oilseed rape in Scania (Figure S8), overall pesticide use (Figure S9) or policy‐driven changes, such as the ban of neonicotinoid seed treatments since 2013 (Lundin, 2021).…”
Section: Discussionmentioning
confidence: 78%
“…It has been shown that diversified landscapes with higher proportions of semi-natural areas exhibit lower pest abundance and/or higher biocontrol services in fields than simple large-scale landscapes with low proportions of non-crop areas (Bianchi et al, 2006;Gagic et al, 2021;Landis et al, 2008;Veres et al, 2013). Although there have been some studies that showed CSFB population increases over the period that the area of the crop has expanded (Collins, 2017;Lundin, 2021;Nilsson, 2002), none have yet clearly related these with increases in OSR grown area. However, it has been shown how pollen beetle (Brassicogethes aeneus) became a troublesome pest after 3-4 years of intensive OSR cultivation and remains so (Hokkanen, 2000); indeed, reproductive success of pollen beetles has increased by 200%-300% during the first 16 years of OSR cultivation compared to those beetles living on cruciferous weeds (their natural host plants; Hokkanen, 2000).…”
Section: Sustainability Issuesmentioning
confidence: 99%
“…Safety assessments of the effects of genetically‐modified crops on bee pollinators in the EU are reviewed 38 . Lundin discusses the Swedish experience in banning oilseed rape seed treatments with neonicotinoid insecticides 39 …”
Section: Figurementioning
confidence: 99%